The poor health of deep‐water species in the context of fishing activity and a warming climate: will populations of Molva species rebuild or collapse?. Issue 6 (10th May 2020) - Lloret, Josep; Serrat, Alba; Thordarson, Gudmundur; Helle, Kristin; Jadaud, Angelique; Bruno, Isabel; Ordines, Francesc; Sartor, Paolo; Carbonara, Pierluigi; Rätz, Hans‐Joachim
Abstract: Many deep‐water fish populations, being K‐selected species, have little resilience to overexploitation and may be at serious risk of depletion as a consequence. Sea warming represents an additional threat. In this study, the condition, or health, of several populations of common ling ( Molva molva ), blue ling ( Molva dypterygia ) and Mediterranean or Spanish ling ( Molva macrophthalma ) inhabiting different areas in the North Atlantic and the Mediterranean was evaluated, to shed light on the challenges these deep‐water species are facing in the context of fishing activity and a warming climate. The data on the condition of Molva populations which are analysed here have been complemented with data on abundance and, for the southernmost species (Mediterranean ling), with two other health indicators (parasitism and hepato‐somatic index). Despite some exceptions ( e.g., common ling in Icelandic waters), this study shows that the condition of many populations of Molva s pecies in the northeastern Atlantic and the Mediterranean Sea has worsened, a trend which, in recent decades, has usually been found to be accompanied by a decline in their abundance. In addition, the poor health status of most populations of common ling, blue ling and Mediterranean ling considered in this analysis points to a lower sustainability of these populations in the future. Overall, the health status and abundance of Molva populations in the northeastern Atlantic and the Mediterranean suggest that only some populations located in the North Atlantic may be able to rebuild, whereas the populations in southern North Atlantic and the Mediterranean, which are probably most at risk from sea warming, are facing serious difficulties in doing so. In the context of fisheries and global warming, this study's results strongly indicate that management bodies need to consider the health status of many of the populations of Molva species, particularly in southern European waters, before implementing their decisions.